Waqf Fundraising Strategy: Segmentation Analysis of Waqf in East Kalimantan - Mahrus, Moh; Musfiroh, Imroh Atul (Borneo International Journal of Islamic Studies, 2023)
Waqf is subject to legal regulation due to its inherent religious nature or the benefits it provides to Muslims. Waqf has significant implications for the development of social structures. The Indonesian Waqf Agency or BWI tend to use market-oriented fundraising strategies with a retail collection approach and an individual communication approach. This discussion focuses on segmentation in efforts to increase waqf fundraising, notably in East Kalimantan. This study uses a qualitative approach. This discussion focuses on segmentation in efforts to increase waqf fundraising, notably in East Kalimantan. There are four samples of BWI representative offices in East Kalimantan. The samples in this study include a BWI representative of Balikpapan, a BWI representative of North Penajaman Paser, a BWI representative of Paser, and a BWI representative of West Kutai. The data collection techniques are observations and interviews to discover in-depth efforts to increase waqf fundraising with segmentation. The data that has been collected was tested for validity using the Triangulation Method technique. Efforts to increase waqf fundraising include determining several waqf donor segments, namely based on geography (area of ​​waqf land, potential of waqf land, potential of the region), demographic (population, number of productive age), social (use of social media, religion and ethnicity), behavior (education and beliefs) and attitudes. On the other hand, the digitalization of waqf using more modern applications, education, and literacy is necessary to facilitate people in waqf.